The Effect of Sports Club Participation on the Students' Somatic Health - Valeriy Hryhoriev (Lesya Ukrainka Volyn National University, 2018)
The implementation of female crossfit for girls and football classes for boys as a part of the sports club participation appears to be prospective for the optimization of the physical education in higher educational institutions and for the somatic health of students. The purpose of the research is to estimate the effect of crossfit and football classes as a part of the sports club participation on the morphofunctional parameters of the physical development and the somatic health of students. The results of the research. It is specified that during the main pedagogical experiment we were observing essential differences in functional parameters of the physical development for students in the experimental group: the growth of lung capacity ratio - by 5,94-8,70 %, handgrip strength - by 5,76-12,60 %, declining resting heart rate by 1,62-5,28 % comparing to the students of the control group where the changes were not significant. In the dynamics of morphological parameters, there were no changes. The comparative analysis of the basic and finite data of the somatic health parameters proved the efficiency of experimental methods. Influenced by them, the students of the experimental groups significantly improved their data: the correlation of lung capacity to body mass - by 3,87-9,61 %, the correlation of handgrip strength to body mass index - by 3,68-13,54 %, Robinson's index - by 1,78-6,23 % and Ruffier's index - by 12,85-16,52 %. The changes in parameters of basic and finite data of the somatic health index of the experimental groups were essentially different from the same parameters of the students in the control groups. Conclusions. Sports club participation in a female crossfit for girls and football classes for boys has a great impact on the physical fitness of student youth specifically on improving morphofunctional parameters of their physical development and the level of the somatic health.